Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1093/rheumatology/30.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence of Carpal Tunnel Syndrome in Oophorectomized Women

Abstract: To determine whether the hormonal changes of the menopause are related to the onset of carpal tunnel syndrome (CTS), 53 healthy women, younger than 44 years, and subjected to bilateral oophorectomy between 1 and 4 years before the study, were evaluated. Seventy healthy menstruating women matched for age were used as controls. In those complaining of symptoms and presenting signs suggestive of CTS, sensory and motor nerve conduction studies were done. In the oophorectomized group, 17 of 53 (32%) had clinical CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Although previous studies have demonstrated that surgical menopause may be a precipitating factor for CTS [7,28], we found that both groups experienced similar frequencies of natural versus surgical menopause. The frequency of natural menopause was significantly higher than surgical menopause in both groups.…”
Section: Discussioncontrasting
confidence: 92%
“…Although previous studies have demonstrated that surgical menopause may be a precipitating factor for CTS [7,28], we found that both groups experienced similar frequencies of natural versus surgical menopause. The frequency of natural menopause was significantly higher than surgical menopause in both groups.…”
Section: Discussioncontrasting
confidence: 92%
“…Women have a three times-increased risk of developing CTS compared with men, especially around the time of menopause. 4,5 Pregnancy, 6 bilateral oophorectomy, 7 and use of the combined oral contraceptive 8 have all been identified as risk factors for CTS. In contrast, menopausal hormone replacement therapy (MHT) has been shown to lead to resolution of CTS in menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical series, CTS has been associated with rheumatoid arthritis, diabetes, hypothyroidism, estrogen replacement therapy (13), oophorectomy (14), and pregnancy (15). Many of these studies have been conducted in highly selected populations and the individual contribution or "attributable risk" from each factor has been small.…”
Section: Introductionmentioning
confidence: 99%